Remediation of Misconceptions with Student Worksheets Based on Cognitive Conflict on Newton's Law Material - Azahra, Audina Paramitha; Wasis, Wasis (Jurnal Pendidikan Fisika, 2024)
This study aims to describe the reduction in student misconceptions regarding Newton's Laws after remediation using student worksheets based on cognitive conflict. The research method used is a pre-experimental design with a One Group Pretest-Posttest format, involving 102 students from three classes at SMAN 12 Surabaya. Data collection was carried out through pretest and posttest, each consisting of five-tier format questions. Data analysis was assisted by SPSS version 25. The significance of the reduction in misconceptions was analyzed using the Wilcoxon test and the Kruskal-Wallis test, as the data were not normally distributed. The results indicated: 1) a significant improvement in understanding between the pretest and posttest, with a high categorization, and 2) all three classes showed comparable improvements in understanding. Based on these findings, it can be concluded that students experienced a significant reduction in misconceptions following remediation using student worksheets based on cognitive conflict.